1980
DOI: 10.1136/bjo.64.10.770
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous dissemination of genital Herpesvirus hominis type 2 to the eye.

Abstract: SUMMARY A 33-year-old man developed Herpesvirus hominis type 2 (HVH-2) eye disease following a herpetic lesion of the penis. The sequence of ocular involvement suggested that the virus had been transmitted endogenously from the genital lesion: granulomatous iritis was followed by interstitial keratitis and then by dendritic keratitis. Recurrent bacterial ulcers ultimately required a conjunctival flap. The course of this man's ocular disease as well as those of other reported cases of HVH-2 adult eye infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…In vivo studies of autoinoculation from one site to another with the patient's own strain of HSV has been demonstrated to cause new foci of disease and reactivation (24). The spread of genital HSV onto the patient's fingers or eyes or onto mucocutaneous sites adjacent to primary genital regions late in the disease course suggests that autoinoculation is a common occurrence (7,14,33). It is unclear why this rate of transmission would be showing such a dramatic increase with time, unless it was concluded that personal hygiene and hand washing practices have changed significantly.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies of autoinoculation from one site to another with the patient's own strain of HSV has been demonstrated to cause new foci of disease and reactivation (24). The spread of genital HSV onto the patient's fingers or eyes or onto mucocutaneous sites adjacent to primary genital regions late in the disease course suggests that autoinoculation is a common occurrence (7,14,33). It is unclear why this rate of transmission would be showing such a dramatic increase with time, unless it was concluded that personal hygiene and hand washing practices have changed significantly.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in adults the virus may be transmitted endogenously from the genital lesion. Some interesting clinical reports suggested hematogenous spread of HSV-2 in healthy adults (Sumers et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, however, a presumptive diagnosis is made on the basis of corneal hypesthesia (18) or opacification (5,26,75) due to a previous herpetic lesion. HHV can also be suspected as the cause if iridocyclitis follows fever (11, 81 ), accompanies cutaneous (28,85) or genital (25,77) lesions, precedes or follows dendritic keratitis (2, 3), is associated with an endothelial plaque (1, 55) or presents as a hemorrhagic iritis (4,7,38,47,48). Anterior uveitis in an eye with other evidence of disease due to HHV should be considered herpetic until another cause is identified (67).…”
Section: Manifestations Of Herpetic Iridocvclitismentioning
confidence: 99%